A contribution to the Reinhart and Rogoff debate: not 90 percent but maybe 30 percent - Sokbae Lee; Hyunmin Park; Myung Hwan Seo; Youngki Shin (Centre for Microdata Methods and Practice (cemmap), 2014)
Using the Reinhart-Rogoff dataset, we find a debt threshold not around 90 percent but around 30 percent above which the median real GDP growth falls abruptly. Our work is the first to formally test for threshold effects in the relationship between public debt and median real GDP growth. The null hypothesis of no threshold effect is rejected at the 5 percent significance level for most cases. While we find no evidence of a threshold around 90 percent, our findings suggest that the debt threshold for economic growth may exist around a relatively small debt-to-GDP ratio of 30 percent. Empirical results are more robust with the postwar sample than the long sample that goes before World War II.
Keywords: H60; F34; E62; 330; Government debt; growth; fiscal policy; median regression; testing